2020
DOI: 10.1111/ors.12490
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anatomical course of the canalis sinuosus using cone beam computed tomography

Abstract: ObjectivesThe aim of this study was to analyse the course of the canalis sinuosus (CS) until its termination in the anterior maxilla and chart its anatomical relationship with surrounding structures using cone beam computed tomography (CBCT).MethodsThis study retrospectively analysed 100 CBCT scans (Accuitomo 170, Morita Corp., Kyoto, Japan) of the maxillary sinuses of patients at the Department of Oral Surgery and Stomatology, School of Dental Medicine, University of Bern. Vertical and horizontal distances be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…One study 27 did not explain how the diameter was measured while other retrospective studies did not investigate diameter. 25,36,38,42,43,[49][50][51][52][53][54] There are only two reports on the presence of more than two CS (one in each quadrant) in a patient. The present study corroborates with von Arx et al 22 and Sekerci et al 34 where 4.08% and 3.3%, respectively, had three CS, while 0.56% and 0.8% of the above studies reported four CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study 27 did not explain how the diameter was measured while other retrospective studies did not investigate diameter. 25,36,38,42,43,[49][50][51][52][53][54] There are only two reports on the presence of more than two CS (one in each quadrant) in a patient. The present study corroborates with von Arx et al 22 and Sekerci et al 34 where 4.08% and 3.3%, respectively, had three CS, while 0.56% and 0.8% of the above studies reported four CS.…”
Section: Discussionmentioning
confidence: 99%
“…Both Manhaes-Junior et al 42 and Tomrukc ßu and K€ ose 40 examined the relationship of CS with the buccal cortical bone, nasal cavity and ridge crest, while Lello et al 52 investigated the IOF, inferior point of the orbital rim and nasal aperture. Gurler et al 37 was the only study that examined the relationship of CS with an impacted tooth, while Lello et al 52 examined its relationship with adjacent structures like the IOF, infraorbital rim and nasal cavity. To our knowledge, the present study is the first to investigate the distance of CS from the closest root apex.…”
Section: Discussionmentioning
confidence: 99%
“…The canalis sinuosus (CS) is a vital neurovascular canal but rarely reports in the literature. 1,2 Jones in 1939, suggested the anatomical feature of CS and describing it as the nerve and blood vessels that leave the infraorbital nerve through the back section of the infraorbital foramen and pass laterally through a 2 mm diameter bone canal beside the nasal cavity. 3,4 The term 'canalis sinuosus' refers to the double-curved course of its structure, which extends for roughly 55 mm through the maxilla.…”
mentioning
confidence: 99%
“…Infraorbital nerve medially bent to anterior wall of the maxillary sinus and passes along the infra-orbital foramen and has a lateral branch (canalis sinuosus), through which the anterior superior alveolar nerve passes. 2,5,7,8 In some cases, the extend of CS in the osseus can form an accessory canal. From study conducted by Machado et al (2016) it was found 52.1% from 1000 patients had accessory canal of CS and Aoki et al (2019) found 66.5 % of 206 patients had CS.…”
mentioning
confidence: 99%
See 1 more Smart Citation